2021
DOI: 10.1093/ijnp/pyab052
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Alters Astrocyte Morphology in Mouse Prefrontal Cortex

Abstract: Background Neuromorphological changes are consistently reported in the prefrontal cortex (PFC) of patients with stress-related disorders and in rodent stress models, but the effects of stress on astrocyte morphology and potential link to behavioral deficits are relatively unknown. Methods To answer these questions, transgenic mice expressing green fluorescent protein (GFP) under the glial fibrillary acid protein (GFAP) promot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 92 publications
8
54
0
Order By: Relevance
“…Albert and Newhouse found that antidepressant therapies in females are affected by estrogen levels (Albert & Newhouse, 2019). (Codeluppi et al, 2021) reported that the behavior changes induced by CRS are sex-specific and that the changes might be related to the stage of the estrus cycle. Furthermore, there are sex differences in the effects of exercise on both brain structures and behavioral tasks (Martini et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Albert and Newhouse found that antidepressant therapies in females are affected by estrogen levels (Albert & Newhouse, 2019). (Codeluppi et al, 2021) reported that the behavior changes induced by CRS are sex-specific and that the changes might be related to the stage of the estrus cycle. Furthermore, there are sex differences in the effects of exercise on both brain structures and behavioral tasks (Martini et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider the role that astrocyte-induced plasticity may be playing in the behavioral sequelae of insults, such as stressors or neurotransmitters (endogenous or exogenous—e.g., synthetic drugs), which, through their receptors located in astrocytes, directly induce intracellular cascades. The latter ultimately introduces changes in the morphology/physiology of astrocytes that alters the normal functioning of tripartite synapses in a pathophysiological direction that is known to drive behavioral sequelae [ 53 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of reports have indicated that chronic and acute stressors alter astrocyte morphology and the expression of astrocyte-specific proteins in brain areas that are known to play a critical role in emotional processing, such as the prefrontal cortex, hippocampus, and amygdala [ 53 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Longer sessions of 24 h induce depressive-like behaviours for more than a month, which are reversible by fluoxetine administration ( Chu et al, 2016 ). Anxiety-like behaviours emerge after 1 week of stress, whereas anhedonic behaviours emerge after 5 weeks of stress ( Codeluppi et al, 2021 ). It has been reported that CRS and CSDS induce similar changes in anhedonic, social-avoidant, and immobile behaviour ( Haenisch et al, 2009 ; Veena et al, 2009 ; Ulloa et al, 2010 ; Voorhees et al, 2013 ; Mao et al, 2022 ).…”
Section: Modelling Pathogenesismentioning
confidence: 99%